2015
DOI: 10.1007/s40489-015-0054-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Impaired Social Motivation Drive Imitation Deficits in Children with Autism Spectrum Disorder?

Abstract: There is clear evidence that children with autism spectrum disorder display deficits in imitation but little consensus on the reasons for these deficits. In this paper, we review evidence that suggests that the presence of imitation deficits may be explained in part by social communication deficits, specifically by impaired social motivation. First, we discuss the social role that imitation serves in typical development and how imitation may facilitate the forming of social connections. Then, we describe evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…At a biological level, this difference is thought to be rooted in the aberrant functioning of neural systems involved in processing social rewards in ASD (Stavropoulos and Carver, 2013). This disruption in social motivational processes has been posited to contribute to imitation deficits in this population (Van Etten and Carver, 2015). Evidence from typical development has indeed demonstrated that people imitate more when they are motivated to affiliate or create rapport with a social partner (for a review, see Chartrand and Lakin, 2013).…”
mentioning
confidence: 99%
“…At a biological level, this difference is thought to be rooted in the aberrant functioning of neural systems involved in processing social rewards in ASD (Stavropoulos and Carver, 2013). This disruption in social motivational processes has been posited to contribute to imitation deficits in this population (Van Etten and Carver, 2015). Evidence from typical development has indeed demonstrated that people imitate more when they are motivated to affiliate or create rapport with a social partner (for a review, see Chartrand and Lakin, 2013).…”
mentioning
confidence: 99%
“…Recent innovative eye-tracking and body-movement analysis studies aim at objectively measuring sensory perception [34], visual orientating preferences [35,36] and imitation abilities [37]. Perception, attention, and imitation impairments are likely to underlie core autistic symptoms [7].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the modeled target actions are imitated more exactly by the infants, even if the actions are irrelevant to achieve a certain outcome or to manipulate an object. Hence, it has been suggested that infants' exact imitation can be used as an indicator of social motivation (e.g., Carpenter, 2006;Van Etten & Carver, 2015). In contrast, alternative theories explain infants' variation in imitative behavior according to what infants interpret as the models' intentions or goals to be: infants imitate the modeled actions more exactly when no other end-state of an action could be perceived as a goal.…”
Section: Introductionmentioning
confidence: 99%